Quality of insulin obtained from hospital and community pharmacies in Mwanza Tanzania: A cross-sectional study - Emmanuel Kimaro; Eveline T. Konje; Benson R. Kidenya; Amani T. Mori; Eliangiringa Kaale (PLoS ONE, 2025)
Background Insulin, a peptide hormone crucial for diabetes management, necessitates strict storage (2-8oC) to maintain concentration, as per regulatory guidelines (e.g., USP, WHO). Degradation can occur during manufacturing process, and transportation or storage, via heat-induced denaturation and aggregation, compromises its efficacy. In Sub-Saharan Africa, including Tanzania, weak regulatory oversight of imported medicines may compromise insulin quality. Varied findings from existing studies underline the need for local quality assessments. Methods This cross-sectional study, conducted from April to July 2024 in Mwanza, Tanzania, evaluated the quality of insulin from eight pharmacies. A convenience sampling approach was employed, with insulin samples purchased as a simulated patient to reflect real-world acquisition. 15 samples, representing seven distinct insulin brands, were collected. High-Performance Liquid Chromatography (HPLC) was utilized to quantify insulin concentration. Additionally, samples were assessed for visual appearance, packaging, labeling, and storage conditions following established pharmacopoeial and quality control standards. Results Out of 15 insulin samples, two samples (13.3%) failed to meet the official USP monograph during the assay test. The remaining samples 13 (86.7%) complied with USP standards. Conclusion These findings underline significant challenges in ensuring the quality of insulin products. While most samples adhered to USP standards, the issues observed highlight the need for improved quality control measures and robust cold chain management to guarantee the efficacy and reliability of insulin for diabetic patients.